2016
DOI: 10.1007/s11910-016-0675-0
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Overview of Limb Apraxia

Abstract: Since the first studies on limb apraxia carried out by Hugo Liepmann more than a century ago, research interests focused on the way humans process manual gestures by assessing gesture production after patients suffered neurologic deficits. Recent reviews centered their attention on deficits in gesture imitation or processing object-related gestures, namely pantomimes and transitive gestures, thereby neglecting communicative/intransitive gestures. This review will attempt to reconcile limb apraxia in its entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“… 161 Regardless, investigating the communicative aspect of pantomime could open new avenues on the interaction between tool use, semantic knowledge and theory of mind. 46 , 237 …”
Section: From Language To Communicationmentioning
confidence: 99%
“… 161 Regardless, investigating the communicative aspect of pantomime could open new avenues on the interaction between tool use, semantic knowledge and theory of mind. 46 , 237 …”
Section: From Language To Communicationmentioning
confidence: 99%
“…In terms of cognitive demands, some studies identified the role of working memory skills 6 or motor imagery 7 in Pantomimes, whereas Intransitive gestures are supposed to rely on social cognitive abilities 8,9 . Halsband and collaborators 10 found that patients with left parietal lesion had more difficulty to perform Intransitive and Pantomime gestures toward the body than those performed away from the body.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this may indicate that diagnosing ideational apraxia in dementia is not sufficient as tool use disorders may be the consequence of a deficit of semantic memory (see, e.g., Ochipa, Rothi, & Heilman, ), planning skills (Poeck, ), inference of function from structure (Spatt et al ., ) or motor dysfunction. Recent works also suggested that recognition of gestures may call for social cognition in some instances (Carmo, Rumiati, & Vallesi, ) which questions the nature of apraxia when additional cognitive deficits are observed (Bartolo & Stieglitz Ham, ). Although it was beyond the scope of this study, it should also be acknowledged that there is still debate between the reasoning‐based approach proposed here and a memory‐based approach according to which tool manipulation relies on stored object–action associations (Rumiati, ).…”
Section: Resultsmentioning
confidence: 99%